2019
DOI: 10.21037/jtd.2018.11.55
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of complications: anastomotic leakage

Abstract: Anastomotic leakage (AL) is one of the most critical and detrimental complications in esophageal surgery. Early diagnosis and timely therapeutic action are necessary if patients are to avoid AL-related problems. However, there is no gold standard or consensus for early diagnosis. In this review, we focus on summarizing the definition and types of AL and modalities for early diagnosis of AL after esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
0
20
0
3
Order By: Relevance
“…Studies have shown that early detection of anastomotic leakage and the formation of a multidisciplinary collaborative group to make treatment decisions reduces the patient mortality rate. 5,6 Therefore, the early identification of anastomotic leakage is of great significance to patient prognosis. Currently, the clinical diagnosis of anastomotic leakage in esophageal cancer primarily includes esophageal endoscopy, barium meal angiography, and staining (methylthionine chloride) swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that early detection of anastomotic leakage and the formation of a multidisciplinary collaborative group to make treatment decisions reduces the patient mortality rate. 5,6 Therefore, the early identification of anastomotic leakage is of great significance to patient prognosis. Currently, the clinical diagnosis of anastomotic leakage in esophageal cancer primarily includes esophageal endoscopy, barium meal angiography, and staining (methylthionine chloride) swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Zur Diagnostik stehen generell klinische und laborchemische Parameter sowie bildgebende Verfahren (Endoskopie, Röntgenkontrastverfahren, Schnittbildgebung) zur Verfügung. Die frühzeitige Identifizierung senkt die Morbidität und Mortalität [ 1 , 2 ].…”
Section: Diagnostikunclassified
“…Clinical presentations of anastomotic leakage are diverse and varies from asymptomatic to severely septic patients. Clinical distinction between anastomotic leakage and other complications such as pneumonia and systemic inflammatory response syndrome (SIRS) is challenging as clinical symptoms are near to identical (11,12). Therefore, leakage is mainly detected using a combination of clinical, endoscopic and radiological evaluation.…”
Section: Introductionmentioning
confidence: 99%